Bridging the Digital Divide: A Study on the Challenges of E-Learning Implementation in Rural and Remote Schools in Indonesia - I Wayan Rediyasa; Syafiq Amir; Zandra Flowers (Journal of Social Science Utilizing Technology, 2025)
Background. The digital divide remains a significant challenge in the context of education in Indonesia, especially in rural and remote areas. While urban schools have increasingly adopted e-learning platforms, many rural schools continue to struggle with limited access to digital resources, inadequate infrastructure, and a lack of digital literacy among both students and teachers. Purpose. This study aims to investigate the challenges faced by rural and remote schools in Indonesia in implementing e-learning and to propose potential solutions to bridge the digital divide. Method. The research utilizes a mixed-methods approach, combining surveys, interviews, and field observations. Data were collected from 15 rural schools across different provinces, involving 300 teachers and 500 students. The quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic coding. The study identifies key challenges, including unreliable internet connectivity, lack of appropriate devices, low levels of digital literacy, and inadequate teacher training. Results. The results highlight that while there is a strong desire to integrate e-learning, the lack of infrastructure and support systems significantly hinders its effectiveness. Despite these challenges, there are instances of innovative solutions, such as community-based internet sharing and local training programs, that have improved the adoption of e-learning in some areas. Conclusion. The study concludes that bridging the digital divide in rural and remote schools in Indonesia requires a comprehensive approach, including infrastructure development, teacher training, and community involvement. Government policies should prioritize equitable access to digital resources to ensure inclusive education for all.